Analisis Semiotika Charles Sanders Peirce Terhadap Pesan Moral Dalam Film Mencuri Raden Saleh Karya Angga Dwimas Sasongko - Mareta Mareta; Nuraida Nuraida; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2023)
Semiotic Analysis of Charles Sanders Peirce Against Moral Messages in the Film Stealing Raden Saleh by Angga Dwimas Sasongko" is the title of the research thesis. Mencuri Raden Saleh is a movie about six young individuals who stole artworks with the intention of making $2 billion in cash. They worked so hard and were so determined to succeed that they eventually succeeded. The formulation of the research issue is how the moral message is shown in the Angga Dwimas Sasongko film Stealing Raden Saleh, while the goal of this study is to discover the moral message portrayed in the Angga Dwimas Sasongko film Stealing Raden Saleh. A qualitative research methodology was applied. Charles Sanders Peirce's semiotic analysis, which focuses on the notion of the triangle of meaning, which is composed of the representamen, object, and interpretant, is the data analysis approach employed. Primary data sources in original DVD/VCD format as well as secondary data sources such books, journals, and the internet serve as the research's primary and secondary data sources, respectively. Using documentation procedures, data collecting methods. The virtues of duty, kindness, compassion, and friendship are among those portrayed in the movie Stealing Raden Saleh. collaboration and accountability. Through this semiotic process, an interpretation is generated that suggests that the next generation has to think critically and creatively, much like Piko and his pals did, who remained together in the face of several challenges.